2021
DOI: 10.1016/j.ultsonch.2021.105775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound treatments on wine microorganisms

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It was observed that the number of bubbles undergoing cavitation per unit of time increases at higher amplitudes, which resulted in a higher inactivation rate of the microorganisms. The majority of the research has been conducted to determine the effect of ultrasound on the microbial inactivation of fruits and vegetables [ 32 , 33 , 34 , 35 ]. The inactivation of microorganisms using heat treatments and ultrasound and their D values (time for 90% reduction of microorganisms) are summarized in Table 1 .…”
Section: Applications Of Ultrasonic Waves In Food Processingmentioning
confidence: 99%
“…It was observed that the number of bubbles undergoing cavitation per unit of time increases at higher amplitudes, which resulted in a higher inactivation rate of the microorganisms. The majority of the research has been conducted to determine the effect of ultrasound on the microbial inactivation of fruits and vegetables [ 32 , 33 , 34 , 35 ]. The inactivation of microorganisms using heat treatments and ultrasound and their D values (time for 90% reduction of microorganisms) are summarized in Table 1 .…”
Section: Applications Of Ultrasonic Waves In Food Processingmentioning
confidence: 99%
“…(Barukčić et al., 2015), Streptococcus thermophilus (Khadem et al., 2020), Hanseniaspora sp. (Al Daccache et al., 2020), Saccharomyces cerevisiae (Munoz et al., 2021), Kluyveromyces marxianus , and Bifidobacterium spp. (Huang et al., 2017).…”
Section: Applications Of Us In Wineries and Wine Processingmentioning
confidence: 99%
“…The ultrasonic system conditions are also crucial factors that influence the effectiveness of this nonthermal emerging technology to be employed in food processes. For instance, Munoz et al (2021) evaluated the effects of the ultrasonic treatment (fluctuating US power, sonication time, and pulses) on vital wine microbiota (Saccharomyces and non-Saccharomyces yeasts and Lactiplantibacillus plantarum bacteria) probed with a piezoelectric transducer at 20 kHz. In the presence of pulses or without pulses, the duration was set at 4, 6, and 8 min at 20%, 50%, and 80% amplitudes, respectively.…”
Section: Microbial Inactivation and Shelf Life Enhancement Of Alcohol...mentioning
confidence: 99%
See 2 more Smart Citations